2020
DOI: 10.3389/fimmu.2020.592325
|View full text |Cite
|
Sign up to set email alerts
|

Defined Intestinal Regions Are Drained by Specific Lymph Nodes That Mount Distinct Th1 and Th2 Responses Against Schistosoma mansoni Eggs

Abstract: uptake and priming characteristics of antigen-positive dendritic cell subsets and the site of infection, which shape the level of Th1 and Th2 responses in order to create a favorable immunological environment for the parasite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 68 publications
2
9
0
Order By: Relevance
“…To investigate whether there was an immune component to the loss of resistance to Tm infection in co‐infected mice we isolated the cMLN most proximal to the caecum (Figure 2A) from naive mice and infected groups at d3, d7, d14, and d20 post‐infection and enumerated the total number of cells present. In our experience this cMLN undergoes the most pronounced hyperplasia following Tm infection, suggesting it as the primary draining MLN for the caecum and/or proximal colon, this is supported by observations from other groups which demonstrate different regions of the intestines drain to specific MLNs 30,32 . As early as d3, mice mono‐infected with Tm displayed increased cellularity of the cMLN relative to naïve mice, with this becoming especially evident at d20 (Figure 2B).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…To investigate whether there was an immune component to the loss of resistance to Tm infection in co‐infected mice we isolated the cMLN most proximal to the caecum (Figure 2A) from naive mice and infected groups at d3, d7, d14, and d20 post‐infection and enumerated the total number of cells present. In our experience this cMLN undergoes the most pronounced hyperplasia following Tm infection, suggesting it as the primary draining MLN for the caecum and/or proximal colon, this is supported by observations from other groups which demonstrate different regions of the intestines drain to specific MLNs 30,32 . As early as d3, mice mono‐infected with Tm displayed increased cellularity of the cMLN relative to naïve mice, with this becoming especially evident at d20 (Figure 2B).…”
Section: Resultssupporting
confidence: 82%
“…In our experience this cMLN undergoes the most pronounced hyperplasia following Tm infection, suggesting it as the primary draining MLN for the caecum and/or proximal colon, this is supported by observations from other groups which demonstrate different regions of the intestines drain to specific MLNs. 30,32 As early as d3, mice mono-infected with Tm displayed increased cellularity of the cMLN relative to naïve mice, with this becoming especially evident at d20 (Figure 2B). By contrast, coinfected mice showed no-increased cellularity of the cMLN at d3, d7, or d14, and whilst they significantly increased the total number of cMLN cells at d20, relative to uninfected controls, they had a significantly lower cell count than the Tm mono-infected group.…”
Section: Co-infection With H Bakeri Reduces Colonic Mln Cellularity B...mentioning
confidence: 99%
“…These findings are supported by observations that basophils isolated from healthy human spleens showed no expression of HLA-DR or costimulatory molecules at steady state or after in vitro stimulation and could not drive T cell proliferation, indicating that human basophil function is restricted to the secretion of soluble mediators (89). However, other studies have suggested that basophils provide help to DC for optimal Th2 induction (75,90,91). As basophils are major producers of IL-4, while DC are not (92), basophils could provide an early source of IL-4 (93), especially in dLN (Figure 2C).…”
Section: Indirect Mechanisms Of Basophilenhanced Antigen Presentationsupporting
confidence: 53%
“…After long-term evolution in mammalian hosts, helminths have developed strategies to survive in the hostile immune environment. It has been shown that helminths have acquired the ability to modulate host immune responses, especially through skewing host immune response to the type-2/regulatory phenotype, in order to escape Th-1-based immune attack [ 21 , 22 , 23 ]. Macrophages play important roles in both innate immune responses and adaptive immunity, as one of the first lines of defense against pathogens [ 24 ].…”
Section: Discussionmentioning
confidence: 99%